2012
DOI: 10.1007/s00280-012-1872-4
|View full text |Cite
|
Sign up to set email alerts
|

An SNP in CYP39A1 is associated with severe neutropenia induced by docetaxel

Abstract: This SNP in CYP39A1 may be a useful biomarker for predicting the risk of docetaxel-induced neutropenia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 24 publications
0
17
1
Order By: Relevance
“…CYP39A1 is one of many CYP enzymes involved in bile acid synthesis from cholesterol [108]. Variants in CYP39A1 have shown a correlation with the incidence of certain adverse toxicities in patients treated with docetaxel [109]. At present further study is required to determine the functional role of CYP39A1 in Bu metabolism and/or treatment-related toxicities and outcomes.…”
Section: Pharmacogenomics Of Busulfan Pkmentioning
confidence: 99%
“…CYP39A1 is one of many CYP enzymes involved in bile acid synthesis from cholesterol [108]. Variants in CYP39A1 have shown a correlation with the incidence of certain adverse toxicities in patients treated with docetaxel [109]. At present further study is required to determine the functional role of CYP39A1 in Bu metabolism and/or treatment-related toxicities and outcomes.…”
Section: Pharmacogenomics Of Busulfan Pkmentioning
confidence: 99%
“…One study reported that simultaneous presence of the CYP3A4*1B and CYP3A5*1A alleles was associated with a 64% increase in docetaxel clearance ( P = 0.0015) . In addition, rs7761731 of CYP39A1 was found to be the only SNP significantly associated ( P = 0.049, OR = 9.0) with the incidence of grade 4 neutropenia among 28 SNP, which were associated with the AUC of docetaxel . The pharmacogenomics of docetaxel have not yet been elucidated in a large clinical study.…”
Section: Pharmacokineticsmentioning
confidence: 99%
“…(36) In addition, rs7761731 of CYP39A1 was found to be the only SNP significantly associated (P = 0.049, OR = 9.0) with the incidence of grade 4 neutropenia among 28 SNP, which were associated with the AUC of docetaxel. (37) The pharmacogenomics of docetaxel have not yet been elucidated in a large clinical study. A genome-wide association study is expected to find genomic variants which relate to the efficacy or toxicity of docetaxel.…”
Section: Pharmacokineticsmentioning
confidence: 99%
“…Therefore, a low CI max indicates the inhibition of these inflammatory reactions. Recently, it has been reported [29, 30] that single nucleotide polymorphisms (SNPs) determine the individual components and/or the total white blood cell count. Furthermore, SNPs may correlate with the incidence of chemotherapy-induced neutropenia.…”
Section: Discussionmentioning
confidence: 99%